Comparison of the Effect of Lullaby and Kangaroo Care on Physiological Criteria during Heel Lance in Preterm Neonates at the Neonatal Intensive Care Unit - Solaleh Alidadian; Mahin Naderifar; Abdolhossein Abbasi; Ali Navidian; Nasrin Mahmoodi (Mashhad University of Medical Sciences, 2021)
Background: The painful procedure of drawing blood from the heel (heel lance) in the neonatal intensive care unit (NICU) is necessary for some diagnostic tests. However, it can have negative effects on the physiological criteria of preterm neonates. This study aimed to compare the effect of lullaby and kangaroo care on the physiological criteria of preterm neonates admitted to the NICU during heel lance. Methods: This clinical trial study was conducted with a crossover design on 60 preterm newborns (30-36 weeks of gestation) admitted to the NICU at Ali ibn Abi Taleb Hospital, Zahedan, Iran, 2019. The neonates were randomly divided into two groups of lullaby and kangaroo care (n=30 each). In the former group, a lullaby was played for the neonates through headphones for 30 min, and in the latter group, the naked neonate was placed in the mother's arms for the same duration. Physiological criteria were recorded before (0 min), during (15 min), and after the procedure (30 min). The collected data were analyzed in SPSS software (version 22) using independent t-tests and Chi-square test. Results: There was no statistically significant difference between the mean scores of gestation age of neonates in the lullaby (32.63±1.92) and kangaroo care (32.69±1.92) group (P=1.000). The results of the independent sample t-test showed that during the intervention, there was a difference between the mean pulse rate (P=0.015), respiration rate (P=0.003), and arterial oxygen saturation percentage (P<0.01) in preterm neonates. The two groups were significantly different in this regard. However, in the post-intervention stage, no statistically significant difference was observed between the mean pulse rate and respiration rate (P=0.60 and P=0.614, respectively). Conclusion: Given the positive effect of kangaroo care on the physiological criteria of preterm newborns during heel lance, this non-pharmacological, low-cost, and available method could help nurses working in the NICU improve physiological criteria during heel lance.